Composition, separator for electrochemical device, electrochemical device, and secondary battery
By using fluorine-containing monomers and amide-containing copolymers on the lithium-ion secondary battery separator, the problem of insufficient heat shrinkability of the separator at high temperature is solved, the safety of the battery is significantly improved, and the heat shrinkage is avoided Short circuit and fire risk.
Patent Information
- Application Number
- CN202380037717.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-19
- Filing Date
- 2023-01-30
- Publication Date
- 2024-12-13
AI Technical Summary
The separator of existing lithium-ion secondary batteries has high heat shrinkage problems at high temperatures, which can easily lead to short circuits and fire risks in the battery.
A copolymer containing fluorine-containing monomer and amide-containing bonds is used as the coating material to improve the heat shrinkage resistance of the separator.
By using copolymers of fluorine-containing monomers and amide-containing bonds, the heat shrinkage resistance of the separator is significantly improved and the safety risk of the battery at high temperatures is reduced.
Smart Images

Figure BDA0005112117000000041 
Figure BDA0005112117000000042 
Figure BDA0005112117000000091
Abstract
Description
Technical Field
[0001] The present invention relates to a composition, a separator for an electrochemical device, an electrochemical device and a secondary battery. Background Art
[0002] Patent document 1 discloses a composite comprising a fluorinated copolymer, an alkali metal salt and an ionic liquid, wherein the fluorinated copolymer is a fluorinated copolymer having a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2) as essential components, and the volatile component is less than 0.1% by mass relative to the entire composite.
[0003] -[CR 1 R 2 -CR 3 R 4 ]-(1)
[0004] (Where R 1 ~R 4 Independently H, F, Cl, CF3, OR 10 (R 10 is an organic group having 1 to 8 carbon atoms). 1 ~R 4 At least one of them is F)
[0005] -[CR 5 R 6 -CR 7 R 8 ]-(2)
[0006] (Where R 5 ~R 8 are independently H, F, an alkyl group having 1 to 3 carbon atoms, a functional group containing a hetero atom other than a fluorine atom, or a group containing the above functional groups. 5 ~R 8 At least one of them is a functional group containing a heteroatom other than a fluorine atom or a group containing the above functional group.
[0007] Patent Document 2 describes a composition characterized by comprising an inorganic filler, a copolymer of a fluorine-containing monomer and a polymerizable vinyl compound having an amide bond, and a solvent.
[0008] Patent document 3 describes an organic-inorganic composite porous diaphragm, which is an organic-inorganic composite porous diaphragm comprising (a) a polyolefin-based diaphragm substrate and (b) an active layer coated with a mixture of inorganic particles and adhesive polymers on one or more areas selected from the group consisting of the surface of the above-mentioned substrate and a part of the pore portion of the above-mentioned substrate, characterized in that the above-mentioned active layer binds the inorganic particles to each other through the adhesive polymer, and forms a pore structure through the gaps between the inorganic particles.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: International Publication No. 2021 / 221113
[0012] Patent Document 2: International Publication No. 2020 / 054210
[0013] Patent Document 3: Japanese Patent Application No. 2008-524824 Summary of the invention
[0014] Problems to be solved by the invention
[0015] An object of the present invention is to provide a composition for coating a separator for an electrochemical device, wherein the composition can improve the heat shrinkage resistance of the separator.
[0016] Means for solving problems
[0017] According to a first aspect of the present invention, there is provided a composition for coating a separator for an electrochemical device, the composition comprising a copolymer containing a fluorine-containing monomer unit and an amide bond-containing monomer unit.
[0018] Effects of the Invention
[0019] According to the present invention, a composition for coating a separator for an electrochemical device, which composition can improve the heat shrinkage resistance of the separator, can be provided. DETAILED DESCRIPTION
[0020] Hereinafter, specific embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.
[0021] The basic structure of a lithium-ion secondary battery is to configure a non-aqueous electrolyte between the positive electrode and the negative electrode as needed through a diaphragm. The diaphragm is located between the positive electrode and the negative electrode to prevent contact between the active materials of the two electrodes, and forms a path for ion conduction between the electrodes by circulating the electrolyte in its pores. In addition, the diaphragm is required to have a function (shutdown function) of blocking the current and preventing excessive current when an abnormal current flows in the battery due to a short circuit between the positive electrode and the negative electrode, and the diaphragm is closed by blocking the microporous membrane when the normal operating temperature of the battery is exceeded.
[0022] In the past, porous films such as microporous polyolefin films composed of polyethylene, polypropylene, etc. were generally used as separators. However, since these polyolefin-based porous films have high heat shrinkage, they have the problem of low dimensional stability at high temperatures. When the internal temperature of the battery rises after the pores in the separator are blocked due to abnormal heating of the lithium-ion secondary battery, there is a concern that the separator may shrink and break, causing an internal short circuit and the risk of fire. In order to improve the safety of batteries at these high temperatures, it is required to improve the heat shrinkage resistance of the separator.
[0023] The present inventors have conducted intensive studies and found that the heat shrinkage resistance of the separator can be improved by coating the separator with a composition containing a copolymer of a fluorine-containing monomer and an amide bond-containing monomer.
[0024] That is, the composition of the present invention is a composition for coating a separator for an electrochemical device, and contains a copolymer of a fluorine-containing monomer and an amide bond-containing monomer. By coating the composition of the present invention on a separator, the heat shrinkage resistance of the separator can be improved.
[0025] (Copolymer)
[0026] The composition of the present invention contains a copolymer of a fluorine-containing monomer and an amide bond-containing monomer.
[0027] Examples of the fluorinated monomer include: (1) 2 Olefins of fluorine atoms bonded to hybrid carbon atoms; (2) monomers represented by the general formula: CH2=CX-COORf (wherein X is Cl, H or an alkyl group, and Rf is a fluoroalkyl group); (3) monomers represented by the general formula: CH2=CH-Rf (wherein Rf is a fluoroalkyl group); (4) monomers represented by the general formula: CH2=CH-ORf (wherein Rf is a fluoroalkyl group), etc.
[0028] Examples of the alkyl group include an alkyl group having 1 to 3 carbon atoms, and a methyl group is preferred.
[0029] The fluoroalkyl group is preferably a linear or branched fluoroalkyl group having 1 to 12 carbon atoms.
[0030] As the fluorine-containing monomer, from the aspect that fluorine atoms bonded to carbon atoms constituting the main chain of the polymer can be introduced into the above copolymer, thereby further improving the heat shrinkage resistance of the diaphragm when the diaphragm is coated, (1) is preferred, and more preferably selected from vinylidene fluoride, trifluoroethylene, tetrafluoroethylene, hexafluoropropylene, trifluorochloroethylene, monofluoroethylene, trifluorostyrene and the general formula: CX2=CXRf 1 (wherein, X is independently H or F, at least one of X is F, Rf 1 At least one selected from the group consisting of fluorinated monomers represented by a linear or branched fluorinated alkyl group having 1 to 12 carbon atoms.
[0031] The fluorinated monomer is more preferably at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene and 2,3,3,3-tetrafluoropropylene, and particularly preferably tetrafluoroethylene, from the viewpoint of further improving the heat shrinkage resistance of the separator when applied thereto.
[0032] The amide bond-containing monomer contains an amide bond and a polymerizable vinyl group. The amide bond is a bond between a carbonyl group and a nitrogen atom. Examples of the polymerizable vinyl group include vinyl, allyl, vinyl ether, vinyl ester, and acryloyl.
[0033] Examples of the amide bond-containing monomer include N-vinyl lactam compounds such as N-vinyl-β-propiolactam, N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, and N-vinyl-enantholactam; non-cyclic N-vinyl amide compounds such as N-vinylformamide and N-methyl-N-vinylacetamide; non-cyclic N-allyl amide compounds such as N-allyl-N-methylformamide and allyl urea; N-allyl lactam compounds such as 1-(2-propenyl)-2-pyrrolidone; and acrylamide compounds such as (meth)acrylamide, N,N-dimethylacrylamide, and N-isopropylacrylamide.
[0034] Examples of the amide bond-containing monomer include
[0035] [Chemistry 1]
[0036]
[0037] (Where R 11 and R 12 are independently H or an alkyl group having 1 to 10 carbon atoms),
[0038] [Chemistry 2]
[0039]
[0040] (Where R 11 and R12 independently represents H or an alkyl group having 1 to 10 carbon atoms).
[0041] As the monomer containing an amide bond, a monomer having a lactam ring is preferred. As the lactam ring, there is no particular limitation as long as it is a ring formed by an amide bond and a carbon atom, and it may be a monocyclic ring or a polycyclic ring, preferably a monocyclic ring. In addition, the lactam ring may have any substituent. As the lactam ring, for example, an α-lactam ring, a β-lactam ring, a γ-lactam ring, a δ-lactam ring, an ε-caprolactam ring, an ω-enantholactam ring, etc. may be cited.
[0042] The amide bond-containing monomer may have a structure in which the atomic group remaining after removing one or more hydrogen atoms bonded to the carbon atom or nitrogen atom forming the lactam ring is directly or indirectly bonded to the polymerizable vinyl group. For example, the amide bond-containing monomer may have a structure in which the atomic group remaining after removing one hydrogen atom bonded to the carbon atom or nitrogen atom forming the lactam ring is bonded to the vinyl group or the allyl group.
[0043] As the monomer containing an amide bond, it is preferred that at least one selected from the group consisting of N-vinyl-β-propiolactam, N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone, N-vinyl-ε-caprolactam and N-vinyl-enantholactam is selected, more preferably at least one selected from the group consisting of N-vinyl-2-pyrrolidone, N-vinyl-2-piperidone and N-vinyl-ε-caprolactam is selected, and N-vinyl-2-pyrrolidone is further preferred.
[0044] The copolymer may contain other monomer units in addition to the fluorine-containing monomer units and the monomer units containing amide bonds. As other monomers, there is no particular limitation as long as they are monomers that can be copolymerized with the fluorine-containing monomers and the monomers containing amide bonds. As other monomer units, vinyl ester monomer units, vinyl ether monomer units, (meth) acrylic acid monomer units with polyethylene glycol in the side chain, vinyl monomer units with polyethylene glycol in the side chain, (meth) acrylic acid monomer units with long-chain hydrocarbon groups, vinyl monomer units with long-chain hydrocarbon groups, etc. can be cited.
[0045] The content of the fluorine-containing monomer unit in the copolymer is preferably 75 to 7 mol % based on the total monomer units, and the content of the amide bond-containing monomer unit in the copolymer is preferably 25 to 93 mol % based on the total monomer units.
[0046] The content of the fluorinated monomer unit in the copolymer is more preferably 60 mol% or less, further preferably 55 mol% or less, particularly preferably 50 mol% or less, most preferably 45 mol% or less, more preferably 15 mol% or more, further preferably 20 mol% or more, particularly preferably 35 mol% or more, and most preferably 40 mol% or more.
[0047] The content of the amide bond-containing monomer unit in the copolymer is more preferably 40 mol% or more, further preferably 45 mol% or more, particularly preferably 50 mol% or more, most preferably 55 mol% or more, more preferably 85 mol% or less, further preferably 80 mol% or less, particularly preferably 65 mol% or less, and most preferably 60 mol% or less.
[0048] The content of other monomer units in the copolymer is preferably 50 mol% or less, more preferably 35 mol% or less, further preferably 25 mol% or less, further preferably 15 mol% or less, particularly preferably 5 mol% or less, and preferably 0 mol% or more.
[0049] Furthermore, the copolymer may be a copolymer containing substantially only a fluorine-containing monomer unit and an amide bond-containing monomer unit.
[0050] The composition of the copolymer can be determined, for example, by 1 H-NMR and 19 F-NMR was used for determination.
[0051] The weight average molecular weight (polystyrene equivalent) of the copolymer is preferably 10,000 to 500,000, more preferably 15,000 or more, further preferably 20,000 or more, particularly preferably 30,000 or more, and more preferably 400,000 or less. The weight average molecular weight can be measured by gel permeation chromatography (GPC) using dimethylformamide as a solvent.
[0052] (Method for producing copolymer)
[0053] The copolymer can be suitably produced by a production method in which a fluorine-containing monomer, an amide bond-containing monomer, and, if necessary, other monomers are polymerized in a reactor.
[0054] As the polymerization method, suspension polymerization, emulsion polymerization, solution polymerization or the like can be used.
[0055] In addition, from the aspect of being able to produce copolymers with high molecular weight, among various polymerization methods, polymerization methods using fluorinated solvents are preferred. For example, copolymers can be appropriately produced by a production method in which at least a fluorinated monomer and an amide bond-containing monomer are polymerized in a fluorinated solvent to obtain a copolymer.
[0056] As the fluorinated solvent, there can be mentioned: hydrochlorofluoroalkanes such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, CF2ClCF2CFHCl; chlorofluoroalkanes such as CF2ClCFClCF2CF3, CF3CFClCFClCF3; perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, CF3CF2CF2CF2CF2CF3, etc. perfluoroalkanes; CF2HCF2CF2CF2H, CF3CFHCF2CF2CF3, CF3CF2CF2CF2CF2H, CF3CF2CFHCF2CF3, CF3CFHCF2CF2CF3, CF2HCF2CF2CF2CF2H, CF2HCF2CF2CF3, CF3CF2CF2CF2CF2 3CF2CF2CF2CF2CF2H, CF3CH(CF3)CF3CF2CF3, CF3CF(CF3)CFHCF2CF3, CF3CF(CF3)CFHCFHCF3, CF3CH(CF3)CFHCF2CF3, CF2HCF2CF2CF2CF2CF2H, CF3CF2CF2CF2CH2CH3, CF3CH2CF2CH3 and other hydrofluorocarbons; F(CF2)4OCH3, F(CF2)4OC2H5, (CF3)2CFOCH3, F(CF2)3OCH3 and other (perfluoroalkyl) alkyl ethers; CF3CH2OCF2CHF2, CHF2CF2CH2OCF2CHF2, CF3CF2CH2OCF2CHF2 and other hydrofluoroalkyl ethers, etc.
[0057] The fluorinated solvent is preferably at least one selected from the group consisting of hydrofluorocarbons, (perfluoroalkyl)alkyl ethers and hydrofluoroalkyl ethers, and more preferably hydrofluoroalkyl ethers, since a copolymer having a higher molecular weight can be produced.
[0058] Among them, the fluorinated solvent is preferably at least one selected from the group consisting of CF3CH2CF2CH3, CF3CH2OCF2CHF2, CHF2CF2CH2OCF2CHF2 and CF3CF2CH2OCF2CHF2, and CF3CH2OCF2CHF2 is more preferable, and CF3CH2OCF2CHF2 is more preferable.
[0059] In the above-mentioned polymerization, a polymerization initiator, a surfactant and a chain transfer agent may be used, and conventionally known ones may be used respectively.
[0060] As the polymerization initiator, a free radical polymerization initiator can be used. As the polymerization initiator, for example, the following substances can be cited as representative examples:
[0061] Dialkyl peroxycarbonates such as di-n-propyl peroxydicarbonate, di-isopropyl peroxydicarbonate and di-sec-butyl peroxydicarbonate;
[0062] Peroxyesters such as tert-butyl peroxyisobutyrate, tert-butyl peroxypivalate, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, and tert-amyl peroxypivalate;
[0063] Dialkyl peroxides such as di-tert-butyl peroxide;
[0064] Di[fluoro(or chlorofluoro)acyl]peroxides; etc.
[0065] Examples of the di[fluoro(or fluorochloro)acyl]peroxides include diacyl peroxides represented by [(RfCOO)-]2 (Rf is a perfluoroalkyl group, an ω-hydroperfluoroalkyl group or a fluorochloroalkyl group).
[0066] Examples of the di[fluoro(or chlorofluoro)acyl]peroxides include di(ω-hydro-dodecafluoroheptanoyl)peroxide, di(ω-hydro-tetrafluorooctanoyl)peroxide, di(ω-hydro-hexafluorononanoyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluoropentanoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl)peroxide, di(ω-chloro-dec ... peroxide, bis(dichloropentafluorobutyryl) peroxide, bis(trichlorooctafluorohexanoyl) peroxide, bis(tetrachloroundecanoyl) peroxide, bis(pentachlorotetrafluorodecanoyl) peroxide, bis(undecanochlorotriacontanoyl) peroxide, and the like.
[0067] By carrying out the polymerization in the presence of a chain transfer agent, the solution viscosity, weight average molecular weight, etc. of the obtained copolymer can be appropriately adjusted. Examples of the chain transfer agent include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol and ethanol; mercaptans such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane.
[0068] The polymerization temperature is not particularly limited, but is preferably 0°C to 95°C, more preferably 15°C to 95°C, from the viewpoint of polymerization rate and cost required for temperature control.
[0069] The polymerization pressure is not particularly limited, but is preferably 0.3 MPaG to 1.5 MPaG, more preferably 0.4 MPaG or more, and even more preferably 1.0 MPaG or less, from the viewpoint of the polymerization rate and the pressure resistance of the reactor.
[0070] When the copolymer is obtained as a slurry after the completion of the polymerization, the copolymer can be recovered by taking out the slurry from the reactor and washing and drying it.
[0071] (Inorganic filler)
[0072] The composition of the present invention preferably further contains an inorganic filler. When the composition of the present invention contains an inorganic filler, the heat shrinkage resistance of the separator can be further improved.
[0073] As the inorganic filler, an inorganic filler containing at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr and Ba is preferred.
[0074] The inorganic filler is preferably at least one selected from the group consisting of metal oxide particles and metal hydroxide particles. In addition, the inorganic filler is more preferably metal oxide particles containing at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr and Ba.
[0075] The metal oxide particles are preferably at least one selected from the group consisting of magnesium oxide, silicon oxide, aluminum oxide, barium oxide, zirconium oxide, and titanium oxide.
[0076] The metal hydroxide particles are preferably at least one selected from the group consisting of magnesium hydroxide, aluminum hydroxide, and zirconium hydroxide.
[0077] Among them, the inorganic filler is preferably at least one selected from the group consisting of magnesium oxide, silicon oxide, aluminum oxide, and zirconium oxide, and more preferably at least one selected from the group consisting of magnesium oxide and aluminum oxide.
[0078] The average particle size of the inorganic filler is preferably 25 μm or less, more preferably 10 μm or less, further preferably 5 μm or less, particularly preferably 1 μm or less, and preferably 0.02 μm or more. The average particle size of the inorganic filler is a value measured using a transmission electron microscope, a laser particle size distribution analyzer, or the like.
[0079] In the composition of the present invention, the content ratio of the copolymer to the inorganic filler [(copolymer) / (inorganic filler)] is preferably 0.1 / 99.9 to 49.9 / 50.1 in terms of mass ratio, more preferably 1 / 99 or more, further preferably 5 / 95 or more, particularly preferably 10 / 90 or more, more preferably 45 / 55 or less, further preferably 40 / 60 or less.
[0080] (Solvent)
[0081] The composition of the present invention preferably further contains a solvent.
[0082] Examples of the solvent include: water; nitrogen-containing organic solvents such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and dimethylformamide; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ester solvents such as ethyl acetate and butyl acetate; ether solvents such as tetrahydrofuran, dioxane, ethyl cellosolve, methyl cellosolve, diethylene glycol dimethyl ether, and triethylene glycol dimethyl ether; aromatic hydrocarbon solvents such as xylene, toluene, and solvent naphtha; aliphatic hydrocarbon solvents such as n-pentane, n-hexane, n-heptane, n-octane, n-nonane, n-decane, n-undecane, n-dodecane, and mineral spirits; mixed solvents thereof; and the like.
[0083] Furthermore, as the solvent, at least one selected from the group consisting of an ester (1) represented by the general formula (1) and a ketone (2) represented by the general formula (2) may be used.
[0084] General formula (1):
[0085] [Chemistry 3]
[0086]
[0087] (Where R 1 and R 2 are independently H, C1~C 10 A straight-chain or branched aliphatic group, or a C6-C 10 Aromatic groups.)
[0088] General formula (2):
[0089] [Chemistry 4]
[0090]
[0091] (Where R 3 and R 4 are independently H, C1~C 10 A straight-chain or branched aliphatic group, or a C6-C 10 Aromatic groups.)
[0092] R in the general formula (1) 1 and R 2 are independently H, C1~C 10 A straight-chain or branched aliphatic group, or a C6-C 10 of aromatic groups.
[0093] R 1The number of carbon atoms of the aliphatic group is 1 to 10, preferably 2 or more, more preferably 3 or more, and preferably 7 or less, more preferably 5 or less. 1 The aliphatic group is preferably an alkyl group. The alkyl group may be linear or branched.
[0094] R 1 The number of carbon atoms of the aromatic group is 6 to 10. The hydrogen atoms bonded to the carbon atoms of the aromatic ring of the aromatic group may be substituted or unsubstituted. Examples of the substituent include alkyl groups such as methyl groups, halogen groups such as chlorine atoms, and the like. 1 The aromatic group is preferably a phenyl group or a benzyl group.
[0095] As R 1 , preferably C1~C 10 A straight-chain or branched aliphatic group, preferably C1 to C 10 A straight-chain or branched alkyl group or a C2-C 10 The straight-chain or branched alkenyl group is preferably a methyl, ethyl, propyl, vinyl, isopropenyl, butyl or pentyl group, and more preferably a propyl, butyl or pentyl group. These groups may be straight-chain or branched, and are preferably straight-chain.
[0096] R 2 The carbon number of the aliphatic group is 1 to 10, preferably 3 or more, more preferably 4 or more, and preferably 8 or less, more preferably 6 or less. 2 The aliphatic group is preferably an alkyl group. The alkyl group may be linear or branched.
[0097] R 2 The number of carbon atoms of the aromatic group is 6 to 10. The hydrogen atoms bonded to the carbon atoms of the aromatic ring of the aromatic group may be substituted or unsubstituted. Examples of the substituent include alkyl groups such as methyl groups, halogen groups such as chlorine atoms, and the like. 2 The aromatic group is preferably a phenyl group or a benzyl group.
[0098] As R 2 , preferably C1~C 10 A straight-chain or branched aliphatic group, preferably C1 to C 10 The straight-chain or branched alkyl group is preferably a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group or a hexyl group, and more preferably a butyl group, a pentyl group or a hexyl group. These groups may be straight-chain or branched, and are preferably straight-chain.
[0099] The ester (1) represented by the general formula (1) is preferably at least one selected from the group consisting of ethyl acetate, ethyl butyrate, butyl methacrylate, propyl propionate, ethyl butyrate, butyl butyrate, butyl valerate, butyl hexanoate, pentyl butyrate, pentyl valerate, pentyl hexanoate, hexyl butyrate, hexyl valerate and hexyl hexanoate, and butyl butyrate is more preferred.
[0100] R in the general formula (2) 3 and R 4 are independently H, C1~C 10 A straight-chain or branched aliphatic group, or a C6-C 10 of aromatic groups.
[0101] R 3 and R 4 The number of carbon atoms of the aliphatic group is 1 to 10, preferably 3 or less, and more preferably 2 or less. 3 The aliphatic group is preferably an alkyl group. The alkyl group may be linear or branched.
[0102] R 3 and R 4 The number of carbon atoms of the aromatic group is 6 to 10. The hydrogen atoms bonded to the carbon atoms of the aromatic ring of the aromatic group may be substituted or unsubstituted. Examples of the substituent include alkyl groups such as methyl groups, halogen groups such as chlorine atoms, and the like. 3 and R 4 The aromatic group is preferably a phenyl group or a benzyl group.
[0103] As R 3 and R 4 , preferably C1~C 10 A straight-chain or branched aliphatic group, preferably C1 to C 10 The straight-chain or branched alkyl group is preferably a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group or a hexyl group, and more preferably a methyl group or an ethyl group. These groups may be straight-chain or branched, and are preferably straight-chain.
[0104] The ketone (2) represented by the general formula (2) is preferably at least one selected from the group consisting of acetone and methyl ethyl ketone.
[0105] As a solvent, water can also be used. For example, when a copolymer is produced by a production method in which monomers are emulsion polymerized in water, a polymer composition containing the copolymer and water is usually obtained, so the water contained in the polymer composition can be used as a solvent for the composition of the present invention.
[0106] Among them, from the perspective of excellent stability and coating properties of the composition, the composition of the present invention preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone, N,N-dimethylacetamide, dimethylformamide, dimethyl sulfoxide, acetone and methyl ethyl ketone, and more preferably contains N-methyl-2-pyrrolidone.
[0107] When the composition of the present invention contains a copolymer and a solvent, the content of the copolymer is preferably 0.1% by mass to 20% by mass, more preferably 1% by mass or more, further preferably 3% by mass or more, particularly preferably 10% by mass or more, most preferably 13% by mass or more, and more preferably 16% by mass or less, relative to the mass of the composition.
[0108] (Other ingredients)
[0109] The composition of the present invention may further contain an organic filler. As the organic filler, a non-conductive cross-linked polymer is preferred, and cross-linked polystyrene, cross-linked polymethacrylate, and cross-linked acrylate are more preferred.
[0110] The composition of the present invention may further contain other polymers such as polyacrylate, polymethacrylate, polyacrylonitrile, polyamideimide, acrylic rubber, carboxyalkyl cellulose, alkyl cellulose, hydroxyalkyl cellulose, and the like.
[0111] (Separator for electrochemical devices)
[0112] By using the composition of the present invention, a separator for an electrochemical device can be produced. The separator for an electrochemical device of the present invention comprises a substrate and a coating layer formed of the above-mentioned composition.
[0113] The substrate and the coating layer may be bonded directly or via other layers, but the coating layer is preferably formed directly on the substrate. The coating layer may be disposed only on one side of the substrate or on both sides. In addition, the coating layer may be disposed in a manner that covers the entire substrate on which the coating layer is disposed or in a manner that covers only a portion of the substrate.
[0114] When the coating layer is formed only on one side of the substrate, the weight of the coating layer is preferably 0.5 g / m2 from the viewpoints of heat shrinkage resistance, adhesion to the electrode, and ion conductivity. 2 ~50.0g / m 2 When the coating layer is formed on both sides of the substrate, the weight of the coating layer is preferably 1.0 g / m 2 More preferably 3.0 g / m 2 Above, preferably 25.0g / m 2 Below, more preferably 20.0g / m 2 the following.
[0115] The thickness of the coating layer per one side is preferably 1 μm to 5 μm. When the thickness of the coating layer is within the above range, the film tearing strength and the insulation properties can be ensured, and the curling of the substrate is less likely to increase.
[0116] As a substrate, a porous substrate with pores or voids inside is preferred. As a porous substrate, a microporous membrane, a porous sheet formed by fibrous objects such as nonwoven fabrics and paper-like sheets, or a composite coating layer formed by stacking more than one other porous layer on these microporous membranes or porous sheets, etc. can be cited. It should be noted that a microporous membrane refers to a film having a structure with multiple micropores inside and these micropores connected, and a gas or liquid can pass from one surface to another.
[0117] The material constituting the substrate may be any one of an organic material or an inorganic material having electrical insulation. In particular, from the aspect of imparting a shutdown function to the substrate, as the constituent material of the substrate, an organic material is preferably used, a thermoplastic resin is more preferably used, and at least one selected from the group consisting of polyethylene, polypropylene, polyimide, polyamide, polyamideimide, polyethylene terephthalate, polyester and polyacetal is further preferably used.
[0118] The shutdown function is a function in which, when the battery temperature rises, the thermoplastic resin melts and blocks the pores of the substrate, thereby blocking the movement of ions and preventing thermal runaway of the battery. As the thermoplastic resin, a thermoplastic resin having a melting point of less than 200° C. is suitable, and polyolefin is particularly preferred.
[0119] As the substrate using polyolefin, a polyolefin microporous membrane is preferred. As the polyolefin microporous membrane, a polyolefin microporous membrane suitable for a conventional non-aqueous secondary battery separator having sufficient mechanical properties and ion permeability can be used. Moreover, from the aspect of having the above-mentioned shutdown function, the polyolefin microporous membrane preferably includes polyethylene.
[0120] The weight average molecular weight of the polyolefin is preferably 100,000 to 5,000,000. When the weight average molecular weight is less than 100,000, it may be difficult to ensure sufficient mechanical properties. When the weight average molecular weight is greater than 5,000,000, the shutdown characteristics may deteriorate and molding may become difficult.
[0121] Such a polyolefin microporous film can be manufactured, for example, by the following method. That is, the process of sequentially implementing (i) extruding a molten polyolefin resin from a T-die and forming a sheet, (ii) the process of implementing a crystallization treatment on the above-mentioned sheet, (iii) the process of stretching the sheet, and (iv) the process of heat-treating the sheet to form a method for a microporous film. In addition, the process of sequentially implementing (i) melting a polyolefin resin together with a plasticizer such as liquid paraffin, extruding it from a T-die and cooling it to form a sheet, (ii) the process of stretching the sheet, (iii) the process of extracting a plasticizer from the sheet, and (iv) the process of heat-treating the sheet to form a method for a microporous film, etc. can also be cited.
[0122] As a porous sheet composed of fibrous materials, fibrous materials composed of polyester such as polyethylene terephthalate, polyolefins such as polyethylene or polypropylene, aromatic polyamide, polyimide, polyether sulfone, polysulfone, polyether ketone, polyether imide and other heat-resistant polymers, or a porous sheet composed of a mixture of these fibrous materials can be used.
[0123] The substrate may be a composite substrate further laminated with a functional layer. The composite substrate is preferred in that it can further add functions through the functional layer. As the functional layer, for example, from the aspect of imparting heat resistance, a porous layer composed of a heat-resistant resin, a porous layer composed of a heat-resistant resin and an inorganic filler can be used. As the heat-resistant resin, one or more heat-resistant polymers selected from aromatic polyamides, polyimides, polyether sulfones, polysulfones, polyether ketones and polyether imides can be cited. As inorganic fillers, metal oxides such as aluminum oxide, metal hydroxides such as magnesium hydroxide, etc. can be preferably used. It should be noted that as a composite method, a method of coating a functional layer on a porous sheet, a method of bonding with an adhesive, a method of thermocompression bonding, etc. can be cited.
[0124] As the substrate, among the above, a porous substrate formed of at least one selected from the group consisting of polyethylene, polypropylene, polyimide, polyamide, polyethylene terephthalate, polyester and polyacetal is preferred.
[0125] From the perspective of obtaining good mechanical properties and internal resistance, the film thickness of the substrate is preferably in the range of 5 μm to 50 μm. The upper limit of the film thickness is more preferably 40 μm, and further preferably 30 μm. In addition, the lower limit of the film thickness is more preferably 10 μm.
[0126] The Gurley value of the substrate is preferably 500 seconds / 100 cc of air or less, more preferably 300 seconds / 100 cc of air or less. The Gurley value is also preferably 50 seconds / 100 cc of air or more. The Gurley value is a value measured using a Gurley densitometer in accordance with JIS P 8117.
[0127] The porosity of the substrate is preferably 30% to 70%, more preferably 35% to 60%. The porosity is a value calculated by the following formula.
[0128] Porosity = (1-sample mass (g) / (sample density (g / cm 3 )×sample volume (cm 3 )))×100
[0129] The sample volume (cm 3 ) is calculated as 10cm×10cm×thickness (cm).
[0130] The average pore size of the substrate is preferably 0.01 μm to 0.5 μm, more preferably 0.1 μm to 0.3 μm. The average pore size is determined by applying the BET formula using a gas adsorption method to measure the specific surface area (m 2 / g), multiplied by the unit area weight of the substrate (g / m 2 ) and calculate every 1m 2 The pore surface area S of the substrate. In addition, the porosity is calculated per 1m 2 The pore volume V of the substrate was calculated using the obtained value to calculate the average pore size (diameter) d from the following formula.
[0131] d=4·V / S
[0132] When the Gurley value, porosity and average pore size of the substrate are within the above ranges, a separator having excellent ion permeability can be obtained, and a battery having good charge and discharge characteristics can be obtained.
[0133] The diaphragm for electrochemical devices can be manufactured by applying the above-mentioned composition on a substrate. The coating method is not particularly limited as long as it is a method that can cover the surface of the substrate with a coating layer formed by the composition. For example, a method of applying the above-mentioned composition on a substrate and drying the coating film can be cited. As a coating method, more specifically, a method of roll-coating the above-mentioned composition on a substrate, a method of immersing a substrate in the above-mentioned composition, and a method of applying the above-mentioned composition to a substrate and further immersing it in an appropriate coagulation liquid can be cited. In addition, the above-mentioned composition can also be used to make a film, and the obtained film is stacked with the substrate by a method such as lamination, thereby manufacturing a diaphragm for electrochemical devices. As a method for making a film using the above-mentioned composition, a method of peeling off after casting the above-mentioned composition on a film with a smooth surface such as a polyester film or an aluminum film can be exemplified.
[0134] The air permeability of the electrochemical device separator is preferably 1000 s / 100 mL or less, more preferably 800 s / 100 mL or less, further preferably 500 s / 100 mL or less, and preferably 50 s / 100 mL or more. The air permeability can be measured using an air permeability tester.
[0135] The Gurley value of the electrochemical device separator is preferably 1000 seconds / 100cc air or less, more preferably 800 seconds / 100cc air or less, and further preferably 500 seconds / 100cc air or less. The above-mentioned Gurley value is also preferably 50 seconds / 100cc air or more. The Gurley value is a value obtained by measuring using a Gurley densitometer according to JIS P 8117.
[0136] The increase rate of the Gurley value of the electrochemical device separator is preferably 500% or less, more preferably 400% or less, and further preferably 250% or less. The increase rate of the Gurley value is also preferably 103% or more. The increase rate of the Gurley value can be calculated by the following formula.
[0137] Gurley value increase rate (%) = (Gurley value of the separator for electrochemical device / Gurley value of the substrate only) × 100
[0138] (Electrochemical Devices)
[0139] The separator for an electrochemical device of the present invention can be applied to an electrochemical device. The electrochemical device of the present invention includes the separator for an electrochemical device.
[0140] As electrochemical devices, batteries such as secondary batteries and capacitors can be cited. The battery can be a primary battery, or a storage battery (secondary battery) or a storage element. The battery can also be a non-aqueous electrolyte battery. Non-aqueous electrolyte batteries include all batteries with electrolytes and power generation elements. As non-aqueous electrolyte batteries, for example, lithium ion primary batteries, lithium ion secondary batteries, nickel-hydrogen batteries, lithium ion capacitors, double-layer capacitors, etc. can be cited.
[0141] The electrochemical device separator of the present invention can constitute a secondary battery together with a positive electrode, a negative electrode and a non-aqueous electrolyte. As a secondary battery, a lithium ion secondary battery is particularly preferred. Hereinafter, a representative configuration when the electrochemical device separator of the present invention is applied to a lithium ion secondary battery is described, but the electrochemical device of the present invention is not limited to these configurations.
[0142] The positive electrode is composed of a positive electrode mixture including a positive electrode active material as a material of the positive electrode and a current collector.
[0143] There are no particular restrictions on the positive electrode active material as long as it can electrochemically embed / de-embed lithium ions. It is preferably a material containing lithium and at least one transition metal, and examples thereof include lithium transition metal composite oxides such as lithium-cobalt composite oxides, lithium-nickel composite oxides, and lithium-manganese composite oxides, and lithium-containing transition metal phosphate compounds.
[0144] The positive electrode mixture preferably further includes a binder, a thickener, and a conductive material.
[0145] As a binder, any binder can be used as long as it is a material safe for the solvent and electrolyte used in electrode manufacturing, and examples thereof include polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, polyethylene, polypropylene, styrene-butadiene rubber, isoprene rubber, butadiene rubber, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, and the like.
[0146] Examples of the thickener include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, and casein.
[0147] Examples of the conductive material for the positive electrode include carbon materials such as graphite, carbon black, carbon nanotubes, and carbon fibers.
[0148] Examples of the material of the positive electrode current collector include metals such as aluminum, titanium, and tantalum, or alloys thereof, among which aluminum or its alloys are preferred.
[0149] The positive electrode can be manufactured by a conventional method, for example, the following method can be cited: the above-mentioned binder, thickener, conductive material, solvent, etc. are added to the above-mentioned positive electrode active material to prepare a slurry-like positive electrode mixture, which is applied to a current collector and pressed after drying to obtain a high density.
[0150] The negative electrode is composed of a negative electrode mixture including a negative electrode material and a current collector.
[0151] Examples of negative electrode materials include: carbonaceous materials capable of inserting / extracting lithium ions, such as thermal decomposition products of organic matter under various thermal decomposition conditions, artificial graphite, natural graphite, etc.; metal oxide materials capable of inserting / extracting lithium ions, such as tin oxide and silicon oxide; lithium metal; various lithium alloys, etc. Two or more of these negative electrode materials may be used in combination.
[0152] As the carbonaceous material capable of intercalating / deintercalating lithium ions, artificial graphite or purified natural graphite produced by high-temperature treatment of graphitizable pitch obtained from various raw materials, or materials obtained by carbonizing these graphites after surface treatment with an organic substance such as pitch is preferred.
[0153] The negative electrode mixture preferably further comprises a binder, a thickener, and a conductive material. As the binder, the same binder as the binder that can be used for the positive electrode can be cited. As the thickener, the same thickener as the thickener that can be used for the positive electrode can be cited. As the conductive material of the negative electrode, metal materials such as copper and nickel; carbon materials such as graphite and carbon black can be cited.
[0154] Examples of the material of the negative electrode current collector include copper, nickel, stainless steel, etc. Among them, copper is preferred from the viewpoint of easy processing into a thin film and cost.
[0155] The negative electrode can be manufactured by a conventional method, for example, the following method can be mentioned: the above-mentioned binder, thickener, conductive material, solvent, etc. are added to the above-mentioned negative electrode material to prepare a slurry, which is applied to a current collector, dried, and then pressed to obtain a high density.
[0156] As the non-aqueous electrolyte solution, a non-aqueous electrolyte solution prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving the electrolyte salt can be used.
[0157] There are no particular limitations on the organic solvent used to dissolve the electrolyte salt, and one or more of hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and vinylene carbonate; and fluorine-based solvents such as fluoroethylene carbonate, fluoroethers, and fluorocarbonates can be used.
[0158] As the electrolyte salt, there can be mentioned LiClO4, LiAsF6, LiBF4, LiPF6, LiCl, LiBr, CH3SO3Li, CF3SO3Li, LiN(SO2CF3)2, LiN(SO2C2F5)2 and cesium carbonate.
[0159] The concentration of the electrolyte salt is preferably 0.8 mol / L or more, more preferably 1.0 mol / L or more. The upper limit depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L.
[0160] The shape of the lithium ion secondary battery is arbitrary, and examples thereof include cylindrical, rectangular, laminated, coin, and large shapes. The shape and configuration of the positive electrode, negative electrode, and separator may be changed according to the shape of each battery.
[0161] Although the embodiments have been described above, it should be understood that various modifications may be made to the embodiments and details without departing from the spirit and scope of the claims.
[0162] <1> According to a first aspect of the present invention, there is provided a composition for coating a separator for an electrochemical device, the composition comprising a copolymer containing a fluorine-containing monomer unit and an amide bond-containing monomer unit.
[0163] <2> According to a second aspect of the present invention, there is provided the composition according to the first aspect, wherein the fluorinated monomer is at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene and 2,3,3,3-tetrafluoropropylene.
[0164] <3> According to a third aspect of the present invention, there is provided the composition according to the first aspect or the second aspect, wherein the amide bond-containing monomer has a lactam ring.
[0165] <4> According to a fourth aspect of the present invention, there is provided a composition according to any one of the first to third aspects, wherein the amide bond-containing monomer is N-vinyl-2-pyrrolidone.
[0166] <5> According to the fifth aspect of the present invention, there is provided a composition based on any one of the first to fourth aspects, wherein the content of the fluorine-containing monomer units of the copolymer is 75 mol% to 7 mol% relative to the total monomer units, and the content of the amide bond-containing monomer units of the copolymer is 25 mol% to 93 mol% relative to the total monomer units.
[0167] <6> According to a sixth aspect of the present invention, there is provided the composition according to any one of the first to fifth aspects, further comprising an inorganic filler.
[0168] <7> According to a seventh aspect of the present invention, there is provided a composition according to any one of the first to sixth aspects, further comprising an inorganic filler containing at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr and Ba.
[0169] <8> According to an eighth aspect of the present invention, there is provided a composition according to any one of the first to seventh aspects, further comprising an inorganic filler, wherein the content ratio of the copolymer to the inorganic filler (copolymer):(inorganic filler) is 0.1:99.9 to 49.9:50.1 in terms of mass ratio.
[0170] <9> According to a ninth aspect of the present invention, there is provided the composition according to any one of the first to eighth aspects, further comprising a solvent.
[0171] <10> According to a tenth aspect of the present invention, there is provided a separator for an electrochemical device, comprising a substrate and a coating layer formed from the composition according to any one of the first to ninth aspects.
[0172] <11> According to an eleventh aspect of the present invention, there is provided the electrochemical device separator according to the tenth aspect, wherein the substrate is formed of an organic material.
[0173] <12> According to a twelfth aspect of the present invention, there is provided an electrochemical device comprising the electrochemical device separator according to the tenth aspect or the eleventh aspect.
[0174] <13> According to a thirteenth aspect of the present invention, there is provided a secondary battery comprising the electrochemical device separator according to the tenth aspect or the eleventh aspect.
[0175] Example
[0176] Next, embodiments of the present invention will be described with reference to examples, but the present invention is not limited to these examples.
[0177] Each numerical value in the examples was measured by the following method.
[0178] <Monomer Composition of Polymer>
[0179] Using an NMR analyzer (Agilent Technologies, VNS 400 MHz), 1 H-NMR and 19 The monomer composition of the polymer was determined in a deuterated chloroform solution state by F-NMR measurement.
[0180] <Weight Average Molecular Weight>
[0181] The measurement was performed by gel permeation chromatography (GPC). AS-8010, CO-8020, columns (three GMHHR-H connected in series) manufactured by Tosoh Corporation and RID-10A manufactured by Shimadzu Corporation were used, dimethylformamide (DMF) as a solvent was flowed at a flow rate of 1.0 ml / min, and the weight average molecular weight was calculated from the measured data (reference: polystyrene).
[0182] <Breathability>
[0183] The measurement was performed using an air permeability tester (manufactured by Kumagai Riki Kogyo Co., Ltd.) The air permeability (s / 100 mL) was calculated by quadrupling the time (s) required for the gas to pass from 0 mL to 25 mL on the scale.
[0184] <Coating thickness>
[0185] The thickness was measured using a high-precision thickness measuring machine (HKT-1240). The film thickness of only the substrate before coating and the film thickness of the separator after coating were measured, and the difference between the values was calculated as the coating film thickness.
[0186] <Area maintenance rate>
[0187] The separators prepared in each experimental example were placed in an oven and heated at 150° C. for 30 minutes. The areas of the separators before and after heating were measured, and the area maintenance rate was calculated by the following calculation formula. A separator having a high area maintenance rate has excellent heat shrinkage resistance.
[0188] Area maintenance rate (%) = (area of the diaphragm after heating) / (area of the diaphragm before heating) × 100
[0189] <Synthesis example 1>
[0190] In an autoclave with a volume of 500 mL, 245 g of HFE-347pc-f (CF3CH2OCF2CHF2), 9.7 g of N-vinyl-2-pyrrolidone, 35 g of tetrafluoroethylene, and 0.5 g of a hydrocarbon solution of 70 wt% tert-butyl peroxypivalate (hereinafter referred to as "Perbutyl PV") as an initiator were added, and a polymerization reaction was carried out at 50°C. When the pressure was reduced from 0.81 MPa to 0.71 MPa by the polymerization reaction, the monomers in the autoclave were purged, and the obtained polymer solution was dried at 120°C, thereby recovering the copolymer (polymer a). The ratio of the polymerization unit based on tetrafluoroethylene / the polymerization unit based on N-vinyl-2-pyrrolidone measured by NMR measurement of polymer a was 38 / 62 (molar ratio), and the weight average molecular weight measured by GPC measurement was 320,000.
[0191] <Synthesis example 2>
[0192] In an autoclave with a volume of 500 mL, 245 g of HFE-347pc-f, 9.5 g of N-vinyl-2-pyrrolidone, 34 g of tetrafluoroethylene, and 1.0 g of Perbutyl PV as an initiator were added, and a polymerization reaction was carried out at 50° C. When the pressure was reduced from 0.77 MPa to 0.66 MPa by the polymerization reaction, the monomers in the autoclave were purged, and the obtained polymer solution was dried at 120° C., thereby recovering the copolymer (polymer b). The ratio of the polymerization unit based on tetrafluoroethylene / the polymerization unit based on N-vinyl-2-pyrrolidone measured by NMR measurement of polymer b was 38 / 62 (molar ratio), and the weight average molecular weight measured by GPC measurement was 240,000.
[0193] <Synthesis example 3>
[0194] In an autoclave with a volume of 500 mL, 245 g of HFE-347pc-f, 7.4 g of N-vinyl-2-pyrrolidone, 38 g of tetrafluoroethylene, and 0.5 g of Perbutyl PV as an initiator were added, and a polymerization reaction was carried out at 50° C. When the pressure was reduced from 0.83 MPa to 0.73 MPa by the polymerization reaction, the monomers in the autoclave were purged, and the obtained polymer solution was dried at 120° C., thereby recovering a copolymer (polymer c). The ratio of the polymerization unit based on tetrafluoroethylene / the polymerization unit based on N-vinyl-2-pyrrolidone measured by NMR measurement of polymer c was 41 / 59 (molar ratio), and the weight average molecular weight measured by GPC measurement was 320,000.
[0195] <Synthesis example 4>
[0196] In an autoclave with a volume of 500 mL, 245 g of HFE-347pc-f, 7.4 g of N-vinyl-2-pyrrolidone, 38 g of tetrafluoroethylene, and 1.0 g of Perbutyl PV as an initiator were added, and a polymerization reaction was carried out at 50° C. When the pressure was reduced from 0.90 MPa to 0.79 MPa by the polymerization reaction, the monomers in the autoclave were purged, and the obtained polymer solution was dried at 120° C., thereby recovering a copolymer (polymer d). The ratio of the polymerization unit based on tetrafluoroethylene / the polymerization unit based on N-vinyl-2-pyrrolidone measured by NMR measurement of polymer d was 41 / 59 (molar ratio), and the weight average molecular weight measured by GPC measurement was 250,000.
[0197] In Examples and Comparative Examples, the following copolymers were used.
[0198] Polymer a (composition ratio: tetrafluoroethylene / N-vinyl-2-pyrrolidone=38 / 62, weight average molecular weight: 320,000)
[0199] Polymer b (composition ratio: tetrafluoroethylene / N-vinyl-2-pyrrolidone=38 / 62, weight average molecular weight: 240,000)
[0200] Polymer c (composition ratio: tetrafluoroethylene / N-vinyl-2-pyrrolidone=41 / 59, weight average molecular weight: 320,000)
[0201] Polymer d (composition ratio: tetrafluoroethylene / N-vinyl-2-pyrrolidone=41 / 59, weight average molecular weight: 250,000)
[0202] Polymer e (composition ratio: tetrafluoroethylene / N-vinyl-2-pyrrolidone=33 / 67, weight average molecular weight: 97,000)
[0203] Polymer f (composition ratio: vinylidene fluoride / hexafluoropropylene = 93 / 7, weight average molecular weight: 320,000)
[0204] Example 1
[0205] Polymer a, alumina powder (average particle size 0.67 μm) and N-methylpyrrolidone (NMP) were mixed in a container at a ratio of 12.2 parts by mass, 18.7 parts by mass and 69.1 parts by mass, respectively, zirconium oxide beads were added, mixed using a bead mill, and then the zirconium oxide beads were filtered to prepare a coating composition.
[0206] In addition, NMP / water was mixed at 55 / 45 to prepare a phase separation liquid. The coating composition was applied to both sides of the polyethylene separator, and the coated separator was immersed in the phase separation liquid for 3 minutes. Next, the separator was immersed in water for 3 minutes and dried in an oven at 80°C for 30 minutes to produce a coated separator. The air permeability and area maintenance rate of the manufactured separator were measured. The results are shown in Table 1.
[0207] Example 2
[0208] A separator was produced in the same manner as in Example 1 except that polymer b, alumina powder (average particle size 0.67 μm) and N-methylpyrrolidone (NMP) were added to the container at a ratio of 15.4 parts by mass, 23.1 parts by mass and 61.5 parts by mass, respectively, and the obtained separator was evaluated. The results are shown in Table 1.
[0209] Examples 3 and 4
[0210] The polymer c and the polymer d were used alone to produce separators in the same manner as in Example 2, and the obtained separators were evaluated.
[0211] Example 5
[0212] After polymer e, alumina powder (average particle size 0.67 μm) and N-methylpyrrolidone (NMP) were mixed in a container at a ratio of 10.0 parts by mass, 15.0 parts by mass and 75.0 parts by mass, respectively, a separator was produced in the same manner as in Example 1 and the obtained separator was evaluated. The results are shown in Table 1.
[0213] Example 6
[0214] After polymer c, magnesium oxide powder (average particle size 0.54 μm) and N-methylpyrrolidone (NMP) were mixed in a container at a ratio of 10.0 parts by mass, 15.0 parts by mass and 75.0 parts by mass, respectively, a separator was produced in the same manner as in Example 1 and the obtained separator was evaluated. The results are shown in Table 1.
[0215] Comparative Example 1
[0216] Using the polymer f, a separator was produced in the same manner as in Example 5, and the obtained separator was evaluated.
[0217] Comparative Example 2
[0218] Using the polymer f, a separator was produced in the same manner as in Example 6, and the obtained separator was evaluated.
[0219] Comparative Example 3
[0220] The polyethylene separator (uncoated raw material) was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0221]
Claims
1. A composition for coating a separator for an electrochemical device, comprising a copolymer comprising a fluorine-containing monomer unit and an amide bond-containing monomer unit.
2. The composition according to claim 1, wherein The fluorine-containing monomer is at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene and 2,3,3,3-tetrafluoropropylene.
3. The composition according to claim 1 or 2, wherein The amide bond-containing monomer has a lactam ring.
4. The composition according to any one of claims 1 to 3, wherein The monomer containing an amide bond is N-vinyl-2-pyrrolidone.
5. The composition according to any one of claims 1 to 4, wherein The content of the fluorine-containing monomer unit in the copolymer is 75 to 7 mol % based on the total monomer units, and the content of the amide bond-containing monomer unit in the copolymer is 25 to 93 mol % based on the total monomer units. 6 . The composition according to claim 1 , further comprising an inorganic filler. 7 . The composition according to claim 1 , further comprising an inorganic filler containing at least one element selected from the group consisting of Mg, Al, Si, Ti, Zr and Ba.
8. The composition according to any one of claims 1 to 7, further comprising an inorganic filler, wherein the content ratio of the copolymer to the inorganic filler (copolymer):(inorganic filler) is 0.1:99.9 to 49.9:50.1 in terms of mass ratio. 9 . The composition according to claim 1 , further comprising a solvent. 10 . A separator for an electrochemical device, comprising a substrate and a coating layer formed from the composition according to claim 1 .
11. The separator for an electrochemical device according to claim 10, wherein The substrate is formed of an organic material. 12 . An electrochemical device comprising the separator for an electrochemical device according to claim 10 or 11 . 13 . A secondary battery comprising the separator for an electrochemical device according to claim 10 or 11 .
Citation Information
Patent Citations
Inorganic composite porous separator film and electrochemical element using the separator film
JP2008524824A
Composition and multilayer body
WO2020054210A1
Complex, polymer electrolyte, electrochemical device, polymer-based solid-state battery, and actuator
WO2021221113A1
